A high resolution γ-ray array for the pandora plasma trap - Goasduff, A.; Santonocito, D.; Menegazzo, R.; Capra, S.; Pullia, A.; Raniero, W.; Rosso, D.; Toniolo, N.; Zago, L.; Naselli, E.; Napoli, D. R. (Frontiers in Physics, 2022)
The measurement of β-decay rates in plasma, simulating stellar-like conditions, is of high 4 interest for the investigation of radionuclides involved in nuclear astrophysics processes. In the 5 new PANDORA plasma trap, these β-decay rates will be estimated by detecting the γ-rays emitted 6 by the daughter nuclei trapped in the confined plasma. The present work describes the high 7 efficiency HPGe detectors array that will be placed around the magnetic trap for this purpose, as 8 well the front-end electronics and acquisition system suitable for the array operation in presence 9 of a high counting rate background originating from Bremsstrahlung radiation.